2021
DOI: 10.5194/bg-18-5831-2021
|View full text |Cite
|
Sign up to set email alerts
|

Fast local warming is the main driver of recent deoxygenation in the northern Arabian Sea

Abstract: Abstract. The Arabian Sea (AS) hosts one of the most intense oxygen minimum zones (OMZs) in the world. Observations suggest a decline in O2 in the northern AS over the recent decades accompanied by an intensification of the suboxic conditions there. Over the same period, the local sea surface temperature has risen significantly, particularly over the Arabian Gulf (also known as Persian Gulf, hereafter the Gulf), while summer monsoon winds may have intensified. Here, we simulate the evolution of dissolved oxyge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 73 publications
1
37
0
Order By: Relevance
“…Trends in the I-RSA and M-RSA show an increase in average SST of approximately 1 • C over 34 years [14], with shallow water areas showing a faster warming trend compared to deep water areas [14,15]. A recent study by Lachkar et al [16] demonstrated that, between 1982-2010, SST has risen by 0.5-1 • C in the O-RSA and by up to 1.5 • C in the I-RSA. Data series from the O-RSA indicate a relatively slower increase of 1.2 • C over the past 50 years in the upper 30 m during the summer monsoon [17].…”
Section: Temperature Salinity and Humiditymentioning
confidence: 97%
See 1 more Smart Citation
“…Trends in the I-RSA and M-RSA show an increase in average SST of approximately 1 • C over 34 years [14], with shallow water areas showing a faster warming trend compared to deep water areas [14,15]. A recent study by Lachkar et al [16] demonstrated that, between 1982-2010, SST has risen by 0.5-1 • C in the O-RSA and by up to 1.5 • C in the I-RSA. Data series from the O-RSA indicate a relatively slower increase of 1.2 • C over the past 50 years in the upper 30 m during the summer monsoon [17].…”
Section: Temperature Salinity and Humiditymentioning
confidence: 97%
“…In the O-RSA, an intensification of suboxic conditions has been linked to greater vertical stratification due to SST warming, which restricts ventilation of the intermediate ocean layer, while strengthening of the summer monsoon wind causes the thermocline depth to rise in the northern Arabian Sea, depleting oxygen in the upper 200 m. Elsewhere in the Arabian Sea, meanwhile, intense summer monsoon winds have the opposite effect of deepening the thermocline and increasing oxygenation [16]. OMZs are expected to expand and intensify during this century, partly in response to climate change [4], and the O-RSA and M-RSA are projected to experience intense deoxygenation, more so than other parts of the Indian Ocean [49,[53][54][55][56].…”
Section: Ph and Dissolved Oxygenmentioning
confidence: 99%
“…The circulation model is based on a configuration of the Regional Ocean Modeling System (ROMS) AGRIF version (Shchepetkin and McWilliams, 2005) thoroughly described in Lachkar et al (2021). The model domain covers the entire Indian Ocean at 1/10°eddy-resolving horizontal resolution and uses 32 vertical layers in terrain-following sigma-coordinates, with enhanced vertical resolution near the surface.…”
Section: Experimental Designmentioning
confidence: 99%
“…The model is spun-up over a period of 145 years allowing a minimal drift in the upper and intermediate ocean. The details of the spin-up strategy and model drift analysis are provided in Lachkar et al (2021).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation